No state shall abridge : the fourteenth amendment and the Bill of Rights - Curtis, Michael Kent, 1942- (Book collections on Project MUSE., 1986)
"The book is carefully organized and well written, and it deals with a question that is still of great importance--what is the relationship of the Bill of Rights to the states."--Journal of American History"Curtis effectively settles a serious legal debate: whether the framers of the 14th Amendment intended to incorporate the Bill of Rights guarantees and thereby inhibit state action. Taking on a formidable array of constitutional scholars, . . . he rebuts their argument with vigor and effectiveness, conclusively demonstrating the legitimacy of the incorporation thesis. . . . A bold, forcefully argued, important study."--Library Journal.